Complete genome sequence of plant growth-promoting Bacillus stratosphericus AIMST-CREST02 isolated from bulk soil of a paddy field - Sivaprakasam, Sumitra; Mohd Azim Khan, Nur Arisa; Fan, Tan Yee; Kumarasan, Yukgehnaish; Sicheritz-Pontén, Thomas; Petersen, Bent; Mohd Hata, Erneeza; Vadamalai, Ganesan; Parimannan, Sivachandran; Rajandas, Heera; Pritchard, Leighton (American Society for Microbiology, 2024)
Here, we present the complete genome of a plant growth-promoting strain, Bacillus stratosphericus AIMST-CREST02 isolated from the bulk soil of a high-yielding paddy plot. The genome is 3,840,451 bp in size with a GC content of 41.25%. Annotation predicted the presence of 3,907 coding sequences, including genes involved in auxin biosynthesis regulation and gamma-aminobutyric acid (GABA) metabolism. © 2024 American Society for Microbiology.